Vitamin D and cardiovascular disease: update and outlook - Pilz, Stefan; März, Winfried (The Scandinavian journal of clinical & laboratory investigation, 2012)
Accumulating evidence suggests that vitamin D may play a role for cardiovascular health. Expression of the vitamin D receptor (VDR) and enzymes for vitamin D metabolism have been identified in the vasculature as well as in the heart. VDR knock-out mice suffer from cardiovascular disease (CVD) and even selective VDR deletion in cardiomyocytes causes myocardial hypertrophy. Many, but not all observational studies showed that vitamin D deficiency is associated with CVD and its risk factors. Low concentrations of 25-hydroxyvitamin D (25(OH)D) are an independent risk factor for cardiovascular events, in particular for strokes and sudden cardiac deaths. Only few randomized controlled trials (RCTs) are available on this topic. These RCTs are frequently limited by the additional supplementation of calcium which may increase the risk of CVD events. RCTs with pure vitamin D supplementation have partially but not consistently shown beneficial effects on cardiovascular risk factors such as arterial hypertension. A number of large RCTs on the impact of vitamin D supplementation on cardiovascular events and mortality have already started but limitations of the study designs such as inclusion of individuals with relatively high 25(OH)D concentrations have to be considered. At present, the evidence is not sufficient for general recommendations to supplement vitamin D in order to prevent and treat CVD. It should, however, be noted that justification for the prevention and treatment of vitamin D deficiency comes from evidence based benefits of vitamin D supplementation on musculoskeletal health.